Who will pay? Inter-generational transfers and public sector pensions - Frank Eich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
This paper analyses the different channels through which particular generations within one society can end up subsidising other generations through the functioning of the welfare state. The welfare state, which is organised and funded by “society” through taxation, plays an important part in almost all countries, often providing services such as education and health care or transfers such as state pensions. Whether a generation receives a net subsidy from another generation (or other generations) can only be determined at the end of their life cycle and not at any particular point in time during their lives. The paper therefore focuses on the flows between the welfare state and generations over their whole lifespan, from birth to childhood, to working life to old age and eventual death. The paper argues that depending on the underlying cause of a potential inter-generational imbalance, the policy response might very well differ. Tax smoothing (and letting debt fluctuate as a buffer) is an appropriate response to varying cohort sizes (the baby boomer example). However, tax smoothing does not help with more structural changes such as the increase in longevity across successive generations. Increasing retirement ages in line with increases in longevity would be one appropriate response as would be making entitlements in old age less generous. In reality many developments take place at the same time so that a policy mix will be required. Last but not least the paper shows that the issue of funded versus unfunded public sector pensions is not as clear cut as some might believe it to be. Perhaps counter intuitively, having unfunded public sector pensions might actually be inter-generationally fairer than having funded pensions. This will depend on the circumstances though.
Keywords: 330; Inter-generational fairness; Labour market; Public finances; Public sector pensions; Government policy